Aglaopheniid hydroids (Cnidaria: Hydrozoa: Aglaopheniidae) from off New Caledonia collected during KANACONO and KANADEEP expeditions of the French Tropical Deep-Sea Benthos Program - Galea, Horia R. (European Journal of Taxonomy, 2020)
Sixteen aglaopheniid hydroids occurring in two recent, deep water collections from off New Caledonia are reported upon, of which 8 species are new, namely Cladocarpus asymmetricus sp. nov., C. partitus sp. nov., C. pennatus sp. nov., Lytocarpia fragilis sp. nov., L. pilosa sp. nov., L. pseudoctenata sp. nov., L. subtilis sp. nov. and Macrorhynchia spiralis sp. nov., the latter producing medusoid gonophores. Although not occurring in the present collections, brief notes on M. disjuncta (Pictet, 1893), including the first description of its gonosome, are provided to support its specific separation from M. phoenicea (Busk, 1852).